2005
DOI: 10.1002/cbic.200400368
|View full text |Cite
|
Sign up to set email alerts
|

A New Ligand for Immunoglobulin G Subdomains by Screening of a Synthetic Peptide Library

Abstract: By screening a synthetic peptide library of general formula (NH(2)-Cys1-X2-X3-X4)(2)-Lys-Gly-OH, a disulfide-bridged cyclic peptide, where X2-X3-X4 is the tripeptide Phe-His-His, has been selected as a ligand for immunoglobulin G (IgG). The peptide, after a preliminary chromatographic characterization, has proved useful as a new affinity ligand for the purification of polyclonal as well as monoclonal antibodies from biological fluids, with recovery yields of up to 90% (90% purity). The ligand is able to bind a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Immobilized APAR on agarose showed a maximum Ab binding capacity of 9.1 mg/mL and gave electrophoretically pure anti-Granulocyte macrophage-colony stimulating factor monoclonal Ab (produced in mouse) in a yield of 95%. Verdoliva et al described the disulfide bridged synthetic peptide (NH 2 -Cys-Phe-His-His) 2 -Lys-Gly-OH, denoted as FcRM, as a ligand for IgG [54]. The dissociation constant of FcRM was reported to be 20 μM and FcRM proved useful as an affinity ligand in the purification of IgG.…”
Section: Immunoglobulin Binding Peptides and Peptidomimeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilized APAR on agarose showed a maximum Ab binding capacity of 9.1 mg/mL and gave electrophoretically pure anti-Granulocyte macrophage-colony stimulating factor monoclonal Ab (produced in mouse) in a yield of 95%. Verdoliva et al described the disulfide bridged synthetic peptide (NH 2 -Cys-Phe-His-His) 2 -Lys-Gly-OH, denoted as FcRM, as a ligand for IgG [54]. The dissociation constant of FcRM was reported to be 20 μM and FcRM proved useful as an affinity ligand in the purification of IgG.…”
Section: Immunoglobulin Binding Peptides and Peptidomimeticsmentioning
confidence: 99%
“…The reported affinity constants are towards IgG. Elution pH of antibody from affinity ligand column: PAM, 3 or 9; Fc-III, 3.5; Fc-III-4C, 3.5; FcRM, 2.7 [42,45,50,51,54]. …”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…Ehrlish and Bailon, and Krook et al also reported IgGbinding peptides discovered using the filamentous phage display technique (5,6). Recently, Verdoliva et al screened a synthetic peptide library and identified an IgG-binding cyclic dimeric peptide that recognized the lower hinge region of IgG (7,8). Of these earlier attempts, the Fc-III peptide with an intramolecular disulfide bond reported by DeLano et al in 2000 (9) is a potential candidate that can displace Protein A functions.…”
mentioning
confidence: 99%
“…The cyclic Fc-III peptide (DCAWHLGELVWCT) (DeLano et al ., 2000), identified by screening a phage display library for binding to Fc, was found to compete effectively with Protein A. Crystallography studies showed that the peptide targeted the C H 2-C H 3 interface of Fc. The cyclic tripeptide (CFHH) 2 KG, selected against mouse IgG and named FcRM, resembled the loop structure of Fc-RIII in binding the lower hinge region (Pro230–Ser239) of the Fc fragment as determined by nuclear magnetic resonance (NMR) (Verdoliva et al ., 2005). Linear peptides with sequences taken from the loop residues of the Fc receptor for bovine IgG2 were tested and modified, with the minimum sequence Phe82–Val85 (FIGV) finally identified for its ability to inhibit the binding of the receptor to bovine IgG2 (Zhang et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%